Media Edugames Berbasis Androidterhadap Kemampuan Pemahaman Konsep Matematis pada Pembelajaran Penyajian Data di Kelas IV SD - Masniladevi Masniladevi; Yullys Helsa; Indah Mai Syarif (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
AbstractThe technological developments that require teachers to create innovative and interactive learning media. A media that is applicative and pleasant that helps students understand mathematical concepts. This study aims to determine the effect of using Android-based Edugames media on the ability to understand students' mathematical concepts. This type of research used Quasi Experimental with the research design of Nonequivalent Control Group Design. The population in this study were all fourth grade students of SD Plus Marhamah Padang. Sampling is done using Puposive Sampling. The instrument used is an Essay test. Based on the calculation of data analysis results of the t-test with a significant level of 0.05 obtained tcount (2.63) > t table (1.68195). the conclusion is that Ha is accepted, which is the effect of using Android-based Edugames media on the ability to understand mathematical concepts in Data Presentation learning in grade IV SD Plus Marhamah Padang. Keywords:. Android-based Edugames Media, Concept Understanding Ability